Pantha prakāsha : khālasā jī dī waḍḍī te pūrī twārīkha, dasāṃ satigurāṃ de pawittra jīwaṇa britānta te khālasā jī de rāja takka de hālāta - Giāna Siṅgha, 1822-1921 (SAMP early 20th-century Indian books project, 1923)
Verse work on the lives and teachings of Sikh gurus and religious leaders.